How do I solve for x when `y = x^(1/3)` and `x^(1/3) - 2x^(-1/3) = 1` 

And how do I simplify:

`(sqrt(3))^-3 + (sqrt(3))^-2 + (sqrt(3))^-1 + (sqrt(3))^0 + (sqrt(3))^1 + (sqrt(3))^2 + (sqrt(3))^3)`


Expert Answers

An illustration of the letter 'A' in a speech bubbles

We are asked to solve `x^(1/3)-2x^(-1/3)=1 ` with the hint to let `y=x^(1/3) ` :

If we let `y=x^(1/3) ` we get:

`y-2y^(-1)=1 `  since `x^(-1/3)=(x^(1/3))^(-1) `

or `y-2/y=1 `  Multiplying by y yields:

`y^2-2=y ==> y^2-y-2=0 `

This factors as `(y-2)(y+1)=0` so we get `y=2` or `y=-1`:

If y=2 then ` x^(1/3)=2 ==> x=8 `

If y=-1 we get `x^(1/3)=-1 ==> x=-1 `

Checking the solutions we see that `8^(1/3)-2(8)^(-1/3)=2-2/2=1 ` and

`(-1)^(1/3)-2/(-1)^(1/3)=-1-2/(-1)=-1+2=1 ` as required.

The solutions are x=8 and x=-1. The graph of `y=x^(1/3)-x^(-1/3);y=1 ` :


One way to simplify `sqrt(3)^(-3)+sqrt(3)^(-2)+sqrt(3)^(-1)+sqrt(3)^0+sqrt(3)^1+sqrt(3)^2+sqrt(3)^3 ` is to use the substitution `y=sqrt(3) ` to get the expression:

`y^(-3)+y^(-2)+y^(-1)+y^0+y^1+y^2+y^3 `

Factoring out a common `y^(-3) ` we get:

`y^(-3)[1+y+y^2+y^3+y^4+y^5+y^6] `

The expression in brackets can be rewritten recognizing the identity:

`y^7-1=(y-1)(1+y+y^2+y^3+y^4+y^5+y^6) ` , so the expression in the brackets becomes `(y^7-1)/(y-1) `

Substituting for y we get ` sqrt(3)^(-3)[(sqrt(3)^7-1)/(sqrt(3)-1)] `

Using the rules for simplifying radical expressions we end up with :

`(40sqrt(3))/9+13/3 `

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial